2020
DOI: 10.1158/1078-0432.ccr-19-3519
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of RAS/MAPK Pathway Cooperates with Trisomy 21 and Is Therapeutically Exploitable in Down Syndrome B-cell Leukemia

Abstract: Purpose: Children with Down syndrome (DS, constitutive trisomy 21) that develop acute lymphoblastic leukemia (DS-ALL) have a 3-fold increased likelihood of treatment-related

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 56 publications
4
19
0
Order By: Relevance
“…The only two samples featuring high wtRAS activity in absence of high JAK2 phosphorylation levels might activate RAS via a different pathway yet to be uncovered for DS-ALL. A very recent novel patientderived xenograft models for DS-ALL found CBL-mutant (wtRAS) cells to have as high ERK1/2-phosphorylation as KRAS-mutant cells [37]. Interestingly in the same study, the leukemia burden in both wtRAS(JAK2-mutant) and mutant-RAS xenograft models was reduced via MEKinhibitor, representing a strongly corroborating evidence to some of the conclusions of our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The only two samples featuring high wtRAS activity in absence of high JAK2 phosphorylation levels might activate RAS via a different pathway yet to be uncovered for DS-ALL. A very recent novel patientderived xenograft models for DS-ALL found CBL-mutant (wtRAS) cells to have as high ERK1/2-phosphorylation as KRAS-mutant cells [37]. Interestingly in the same study, the leukemia burden in both wtRAS(JAK2-mutant) and mutant-RAS xenograft models was reduced via MEKinhibitor, representing a strongly corroborating evidence to some of the conclusions of our study.…”
Section: Discussionsupporting
confidence: 89%
“…Functional consequences of an increased dose of some chromosome 21 genes may play important roles [48], and this is discussed in greater detail in "Supplementary Discussion". It will be important to unravel the mechanisms behind the actions of these chromosome 21 genes, as their specific inhibition may be an additional component to consider in combinatorial therapy approaches [37,49]. This is highlighted by very frequent observations of extra copies of chromosome 21 as acquired changes in DS and non-DS ALL, both at diagnosis, and at relapse [20,50].…”
Section: Discussionmentioning
confidence: 99%
“…While a copy number gain of DYRK1A is expectedly seen in ALL and acute myeloid leukemia (AML) cells with abnormalities such as hyperdiploidy (e.g., MHH-CALL-2), hypertetraploidy (e.g., TALL-1), and DS (e.g., CMK), cells without gain of HSA21 also have increased DYRK1A expression, indicating that this dysregulation may occur at the transcriptional level (Figure 1B). Moreover, we found that DYRK1A protein levels were increased in both B-ALL cell lines and in patient cells (22) compared with normal human bone marrow mononuclear cells (BMMCs) (Figure 1C). A query of the pediatric cancer data set in St. Jude GenomePaint (23) demonstrated that increased DYRK1A expression is associated with worse EFS in several subtypes of B-ALL, such as hyperdiploid (HeH) and Ph-like ALL (Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/JCI135937DS1), underscoring its potential role as a prognostic and therapeutic target.…”
Section: Resultsmentioning
confidence: 96%
“…We performed an in vitro kinase assay, which validated that DYRK1A phosphor-malignant B cells. The effect of DYRK1A inhibition was most striking in MHH-CALL-4 and MUTZ-5 cells, as well as in PDX cells harboring gain of HSA21 (DS-ALL-02 and HeH-ALL-09) (22), in which the IC 50 values were in the high nanomolar range. Moreover, compared with previously published DYRK1 inhibitors, including harmine (32) and INDY (33), EHT 1610 displayed more potent activity in B-ALL, T cell ALL (T-ALL), and, particularly, DS-ALL samples (Figure 2H and Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation